Synthesis of Ajoene Analogues by Novel Synthetic Strategies. Issue 9 (19th January 2021) - Yamamoto Raynbird, Marina; Khokhar, Shaista S.; Neef, Daniel; Evans, Gareth J. S.; Wirth, Thomas
Abstract: Ajoene is a compound found in garlic extracts exhibiting a large range of biological activity. Novel ajoene analogues have been prepared in the search of compounds with superior bioactivity. Modifications include the alteration of the sulfoxide, the central alkene and the terminal allyl groups. Abstract : Non‐natural Allium analogues of three types have been synthesised by novel synthetic strategies. Analogues have been biologically evaluated in their ability to inhibit biofilm production in S. Aureus and P . Aeruginosa with promising results.